Total Cost Dan Net Profit Margin Usaha Abon Ikan Madurasa Provinsi Papua Barat - Usman, Sarah; Bawole, Roni; Rahayu, Mudji; Tururaja, Tresia; Matulessy, Marthin (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The purpose of the study is to see how much the total cost and net profit margin issued by the Madurasa abon business.The results of the study obtained a total cost of Rp. 7,041,850 using 14.6% fixed cost and 85.4% variable cost. Percentage of production costs not standardized or production Based on orders. NPM is 57.68%. This means that the profits obtained have the potential in the future. However, there is still a large allocation of variable costs. Where the variable cost should have a smaller value than the fixed cost. This means that in carrying out production and cost management, there is still no good standardization in terms of time and costs incurred.